Small and Medium Enterprises in the Russian Transaction Sector - I. M. Gurova (Модернизация, инновация, развитие, 2019)
Purpose: to study the significance of small and medium enterprises for the functioning of the modern Russian transaction sector.Methods: the paper used General scientific research methods: analysis and synthesis, abstraction, generalization. The study used a comparative method and elements of economic analysis. The article also uses a graphical method of presenting information. The study was carried out on the basis of official statistical data provided by the Federal State Statistics Service of Russia.Results: to achieve this goal, the article solves the following tasks: 1) A review analysis of the current state of the domestic transaction sector based on the study of statistical data on the activities of Russian enterprises and organizations. This formed the basis for further research. 2) Analyzed indicators of small and medium enterprises in the transaction types of economic activity. This made it possible to identify their role in the functioning of the transaction sector. 3) Studied the statistical indicators of the financial condition of small and medium organizations of the transaction sector, which showed the problems of their activities.Conclusions and Relevance: currently, the transaction sector is a significant part of the domestic economy. This is evidenced by a General analysis of the statistical characteristics of the activities of Russian enterprises and organizations. At the same time, the majority of enterprises engaged in transactional activities have a private form of ownership. The study of the activities of small and medium enterprises showed that today more than half of them work in the transaction areas. In this regard, small and medium businesses can be considered an integral and very important part of the modern transaction sector. The flagship of the transactional activity in the business environment is small businesses. Their indicators significantly exceed the corresponding values of medium organizations. In addition, the main role of small enterprises is due to the immanent properties of small-scale companies. Nevertheless, the analysis of indicators of the financial condition of small and medium enterprises of transaction activities revealed their weak business and commercial efficiency, the presence of problems of solvency and financial stability. This threatens not only the viability of enterprises, but also the efficient functioning of the transactional sector. In this regard, there is a need to develop and conduct systemic activities aimed at supporting the development of Russian small and medium enterprises, as well as stimulating the development of the entire domestic transaction sector, consistent with the general strategy of economic development of Russia.